Estudio piloto de una intervención grupal cognitivo-conductual para prevenir depresión en adultos (2020)
The aim of the study was to validate the adaptation of a program of group intervention based on problem-solving to prevent depression in adults on a pilot study level. It had two samples: 3 judges, clinical psychologists, that knew the problem-solving model and had at least 10 years of experience in clinical attention; and 4 potential users, women, with ages between 27 and 31 years (M = 29; DE = 1.6), employees, that presented depressive symptoms. The study had a component of validation through judges using the Angoff method, during 3 sessions they assessed 55 characteristics of the program looking for consensus; and other, of application to potential users, with pre-test, post-test and following measure after a month. First, an adaptation from the original program was made, and then validated by the judges. Later, an initial interview with potential users was carried and those interested that fulfilled the inclusion criteria made the group that received the intervention of 5 sessions of 90 minutes imparted twice a week. The program is built adequately and can be effective in spite of the fact that significant differences between participants’ depressive symptoms were not found after the treatment (X2(n = 4) = 5.286; p = 0.071). The results are an asset to enrich, adjust and later on, assess the program in different populations that allow to obtain empirical evidence that acknowledge it as an effective and of wide range tool to prevent depression in Colombians.